Training on Local Potential Development of Banana Peel Crackers, Increasing Confidence in Halal Sales and Management Procedures for Female Heads of Households in Cukir Village, Diwek, Jombang - Chusnul Rofiah; Erminati Pancaningrum; Sapto Roedy Widijanto (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Training on Local Potential Development of Banana Peel Crackers was carried out in Cukir Village, Diwek, Jombang, with the main aim of increasing the self-confidence of women heads of families in the field of sales and understanding halal management procedures. Banana peels, which are usually waste, are processed into products of high economic value in the form of crackers, thereby providing new business opportunities for the participants. This training includes techniques for processing banana peels into crackers, marketing strategies, and knowledge about halal certification which is important to increase product competitiveness in the market. The results of the training showed an increase in participants' skills and knowledge in making products, increased confidence in selling, and a better understanding of the importance of halal management. Thus, this program not only contributes to improving the household economy but also supports sustainable local industrial development.